Disease activity indexes might not capture the same disease aspects in males and females with ankylosing spondylitis: A real-world nationwide analysis - Fernández-Carballido, Cristina; Jovaní, Vega; Catalán, Emma Beltrán; Moreno-Ramos, Manuel José; Sanz Sanz, Jesús; Gallego, Adela; García Vivar, M. Luz; Rodríguez-Heredia, José Manuel; Sanabra, Cristina; Sastré, Carlos (Frontiers in Medicine, 2022)
Background: To evaluate gender differences in disease activity and health status (HS) in patients with radiographic axial spondyloarthritis (r-axSpA)/ankylosing spondylitis (AS). Methods: Ancillary analysis of the MIDAS study, an observational, non-interventional, cross-sectional and retrospective multicenter nationwide study to assess disease activity and its relationship with HS in clinical practice. Adult patients with AS diagnosis, fulfilling ASAS and modified New York criteria, treated for ≥3 months upon study inclusion according to clinical practice were included. The primary outcome was “disease control” assessed by the percentage of patients in remission and low disease activity (BASDAI and ASDAS-CRP scores). HS was evaluated using the ASAS health index (ASAS-HI). Patients’ responses and characteristics were analyzed by gender. Results: We analyzed 313 patients with AS, 237 (75.7%) males and 76 (24.3%) females. A total of 202 (64.5%) patients had adequate disease control (BASDAI<4); 69.2% of males (mean (SD) BASDAI 2.9 (2.1)) and 50.0% of females (mean (SD) BASDAI 3.8 (2.4); p=0.003). According to ASDAS-CRP, 57.5% of patients were adequately controlled (ASDAS-ID +ASDAS-LDA); 138 (58.2%) males and 42 (55.3%) females. The mean (SD) ASDAS-CRP was 1.9 (1.1); being 1.9 (1.0) in males and 2.0 (1.1) in females. Overall, the impact of AS on HS was low to moderate (mean (SD) ASAS-HI 5.8 (4.4)); being 5.5 (4.4) for males and 6.8 (4.2) for females (p=0.019). Conclusion: This study showed a higher proportion of females with AS and active disease using the BASDAI definition. When using the ASDAS-CRP definition these differences by gender were less pronounced.